Meningkatkan Hasil Belajar Siswa pada Materi Gerak Lurus Melalui Penerapan Model NHT di Kelas X MIPA SMAN 1 X Koto Diatas - Ahmad Topan (Eduscience Development Journal, 2022)
This research aims to increase the student’s learning achievement about a straight movement by applying the NHT model at grade X of natural. Science class I Physics is one of the subjects that are not interesting to some of the students of SMAN 1 X Koto Diatas. Because it is considered a complicated subject, they tend to be passive in joining physics classes. To increase the student activeness in physics, it is needed a proper learning model. One of the models to improve students’ activeness is the NHT model. This research is action research by having collaboration between the researcher and the researcher and the physics teacher. The subject research is 34 students of SMAN 1 X Koto Diatas, grade X of natural science class I In the year of 2021/2022. The technique of data collection uses students’ activities observation space and students’ test marks. The data is analyzed qualitatively by using the percentage technique. The research result shows that by applying the NHT model to the material of straight movement at grade x of natural science I at SMAN 1 X Koto Diatas. There is an increase to : (1). The student’s activities at cycle I that is 72,9%, then at cycle 2 it becomes 95 %, the percentage increase is 22,9%. (2). Teacher’s activeness at the first meeting was 73,07% and increased in the fourth meeting to 90,74 %. It increases by 17,67 % with a very good predicate, and (3). The student learning achievement, in cycle 2 there are five students (14%) who got excellent scores, 25 students(69,5%) got good scores, five students (14%) got a middle score, and there is only an I student (24,77 %) got the lowest score.